Essential Concepts in Sociology (excerpts) - Anthony Giddens; Philip W. Sutton (Journal of Economic Sociology, 2018)
Social life has been changing, that is why sociology cannot stay put. Today, this research field is unbelievably multifaceted from the theoretical point of view; it covers a lot of topics and uses wide methodological tools. Key concepts and ideas play an important role in how sociologists explore societies. However, essential concepts have constantly evolved and changed. This book introduces essential concepts, presenting the basics of sociology as a field. The authors consider each concept in detail, providing not only short vocabulary definitions, but also including historical and theoretical contexts of its emergence and usage, demonstrating meanings and interpretations, and addressing critics and evolution in modern research and theories. This book’s structure allows readers to bridge a history of sociology and its current conditions, tracing the evolution of its concepts. The authors thoroughly selected 70 concepts. The book chapters are divided into 10 main topics. Within each topic, concepts are listed in alphabetical order. This makes searching for a concept easier and more comfortable.The Journal of Economic Sociology publishes the book’s fourth theme, “Structures of Society,” in which the author reviews bureaucracy, capitalism, consumerism, organization, labor division, education, and religion.